Porous silicon derived from 130 nm Stöber silica as lithium‐ion battery anode. Issue 8 (8th February 2021) - Zuo, Xiuxia; Cheng, Ya‐Jun; Zhu, Jin; Gao, Jie; Xia, Yonggao
Abstract: Micro‐sized porous silicon‐based anode materials gain much interest due to good cycling stability, high rate performance, reasonable tap density and low processing cost. Self‐templating process is developed to construct micro‐sized macro‐/mesoporous silicon through magnesiothermic reduction of Stöber silica. The size of the silica particles plays a vital role in the structure control of the porous silicon. In this work, silica particles with a diameter of 130 nm are used as templates to guide the synthesis of micro‐sized macro‐/mesoporous silicon. The magnesiothermic reduction temperature is varied in a systematic way to reveal the self‐templating mechanism comprehensively. It is found that the silica particles with small diameter of 130 nm still exercise the self‐templating effect during the magnesiothermic reduction process in the temperature range of 700 to 900°C. Based on the experimental results, the structure‐property correlation of the porous silicon anode is unveiled. Improved electrochemical performance is demonstrated by the porous silicon compared to the commercial nano‐sized silicon. Abstract : Micro‐sized porous Si anode materials are synthesized based on the self‐templating mechanism via magnesiothermic reduction of 130 nm silica, which show improved electrochemical performance compared with the commercial nano‐sized Si and micro‐sized Si.